Compressive strenght of hybrid composites and nanofilled composites after post curing using light box - Rizany, Tirza; Fadil, Mochammad Richata; Sukartini, Endang (Faculty of Dentistry Universitas Padjadjaran, 2010)
Introduction: Nanofilled composite resins and resin hybrid composites are often used for the manufacture of composite indirect restorations because it has the addition of filler to add strength materials. This study aimed to compare the compressive strength of composites and composite hybrid nanofilled after post curing using light box. Methods: The research conducted was experimental research, with samples divided into two groups of each 10 specimens of hybrid composite resin and nanofilled. Composite cylindrical diameter of 3mm and 6mm high in post-curing for 180 seconds using a light box compressive strength test was then performed using a Lloyd Instruments LRX Plus, 1 mm/mnt speed. Results: The results were the average compressive strength of post-curing hybrid composites 234.61 MPa higher than the average post-curing composite nanofilled that was 196.60 MPa. Conclusion: the compressive strength of hybrid composite after post curing with light box is greater than the nanofilled composite.